The Structure of Morphemes of Lithuanian Verbs - Kazlauskienė, Asta; Raškinis, Gailius (Respectus Philologicus, 2013)
The aim of this research was to establish and describe the most important phonemic patterns of Lithuanian verb morphemes. The investigation was based on a corpus of 30,000 verb types (verbs and their forms). All words in the corpus were stressed and phonetically transcribed. A computer program was developed to extract statistics out of this corpus. The results indicate that monosyllabic morphemes dominate in Lithuanian. They comprise 97%, 99%, 98%, and 97% of all verb roots, prefixes, derivational suffixes, and endings respectively. Inflectional suffixes and the reflexive affix are exclusively monosyllabic. Pronominal inflection endings are either disyllabic (97%) or trisyllabic. There is a high variety of vowelconsonant patterns among verbs: the verb root is represented by 91 patterns, prefixes by 8 patterns, derivational suffixes by 18 patterns, inflectional suffixes by 7 patterns, inflectional endings by 9 patterns, endings of pronominal participles by 7 patterns, and the reflexive affix by 3 different patterns. The consonant-vowel-consonant (CVC) pattern appeared to be the most frequent among verb roots (45%), the CV pattern was the most frequent among prefixes (59%), the VC pattern was the most frequent among derivational suffixes (46%), and V pattern was the most frequent among inflectional endings of Lithuanian verbs (76%). In many cases, the root of a verb contains both initial and final consonants (82%). Because of this and because of the tendency to avoid hiatus in Lithuanian, the root can be adjoined by vowel-final prefixes and vowel-initial suffixes or inflectional endings. This appears to be the case, as prefixes are mostly open (80%), and both derivational suffixes (90%) and all inflectional endings begin with vowels. Inflectional suffixes do not follow this regularity. Only one-third of them start with a vowel. The hypothesis that the phonemic structure of a verb root might determine the corresponding patterns of its adjoining affixes seems to be supported by this investigation.